Tourism Development Strategy in Pasuruan Regency - Hana Farasastin; Ilmi Usrotin Choiriyah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2020)
Regional development is an integral part of national development in accordance with the mandate of Law number 33 of 2004 concerning financial balance between the central government and regional governments where regions can manage their own households to accelerate the realization of community welfare. Therefore, the Regional Government is given the authority to explore its own sources of income. PAD consists of the results of regional taxes, the results of regional levies, the results of separated regional wealth management and other legitimate regional income. In Pasuruan Regency the tourism sector has not become a major contributor to PAD so that in order to achieve this goal the Pasuruan Regency Culture and Tourism Office requires a tourism development strategy. The purpose of this study is to analyze and describe tourism development strategies by the Pasuruan Regency Culture and Tourism Agency in increasing PAD. The method used is a qualitative method with data collection carried out by means of observation, interviews and documentation. The results of this study state that there are several types of strategies namely Corporate Strategy, Strategy Program, Resources Support Strategy and Institutional Strategy in tourism development carried out by the Culture Service and Pasuruan Regency Tourism in increasing PAD in Pasuruan Regency. Of the four types of strategies in Pasuruan Regency the most prominent strategies are Corporate Strategy and Strategy Program.